Evaluasi Kesesuaian Rencana Penambangan Dengan Realisasi di Tambang Ks-1 PT. ABC Kabupaten Barito Utara Provinsi Kalimantan Tengah - Ni Putu Ayu Indyastika; I Putu Putrawiyanta; Yunida Iashania; Yosa Yonathan Hutajulu; Saptawartono Saptawartono (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to evaluate the level of conformity between the mining plan and its actual implementation in Pit Ks-1 of PT. ABC during the period of April 2025. The evaluation was conducted to determine the level of production achievement and to identify the factors causing discrepancies between the planned design and the actual field conditions. The research employed a descriptive-quantitative method, utilizing mine planning software to analyze and compare the planned mining sequence with the actual progress in the field. The analysis focused on the conformity between the planned mining sequence and the actual pit conditions, as well as the achievement of production targets. The results show that the actual overburden removal reached 872,819 bcm or 89% of the target of 981,990 bcm, while coal production reached 38,130 tons or 54% of the target of 70,000 tons. Based on the evaluation of the mining sequence conformity, the study area was dominated by undercut conditions (insufficient excavation), with a smaller portion of overcut (excess excavation), and several areas that were in plan (aligned with the design). The main factor contributing to the discrepancy between the plan and the actual mining realization was environmental conditions, particularly the high rainfall intensity during the study period. The total rainfall hours exceeded the planned working schedule, resulting in reduced Effective Working Hours (EWH). This condition caused slippery haul roads and flooded pit fronts, which hindered equipment movement and lowered operational productivity.